2023
DOI: 10.3390/nu15071753
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Intake and Circulating EPA and DHA Concentrations in US Pregnant Women

Abstract: In the United States, pregnant women have low concentrations of docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), which are essential for fetal development. Although maternal blood provides accurate polyunsaturated fatty acid (PUFA) concentrations, venipuncture is expensive and not always accessible. Thus, this study aimed to determine the association between maternal self-reported dietary intake of foods high in DHA and EPA with maternal blood concentrations. Pregnant women (13–16 weeks gestation) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Women self-reported their dietary intakes at enrolment (13-16 weeks into pregnancy) and at 36 weeks into gestation (32). It was found that polyunsaturated fatty acid consumption decreased from early to late pregnancy which was attributed to a decline in the nutritional quality of diets as pregnancy progressed (32). This is interesting given that sex hormones and physiological changes associated with pregnancy can increase liver enzymes involved in DHA synthesis (33).…”
Section: Intakes Of O3lc-pufasmentioning
confidence: 99%
See 2 more Smart Citations
“…Women self-reported their dietary intakes at enrolment (13-16 weeks into pregnancy) and at 36 weeks into gestation (32). It was found that polyunsaturated fatty acid consumption decreased from early to late pregnancy which was attributed to a decline in the nutritional quality of diets as pregnancy progressed (32). This is interesting given that sex hormones and physiological changes associated with pregnancy can increase liver enzymes involved in DHA synthesis (33).…”
Section: Intakes Of O3lc-pufasmentioning
confidence: 99%
“…In the United States (US) recent research measured EPA and DHA blood concentrations across pregnancy (32). Women self-reported their dietary intakes at enrolment (13-16 weeks into pregnancy) and at 36 weeks into gestation (32).…”
Section: Intakes Of O3lc-pufasmentioning
confidence: 99%
See 1 more Smart Citation